The Effectiveness of Behavioral Counseling Theory with Modeling Tecniques to Improve The Character Able to Independent Through Lesson Study - Irda Laila; I Ketut Dharsana; Ni Ketut Suarni (International Conference on Technology and Educational Science)
This study aims to determine the effectiveness of behavioral counseling modeling techniques to improve the character able to independent characters through lesson. This research is a quasi research ("Quasi Experiment"). The purpose of this study was to determine the effectiveness of modeling techniques in behavioral counseling models for able to independent of UPW B grade X students. The process of collecting data in this study used observation sheets, interview sheets, diaries and character able to independent questionnaires. The results of this study experimental group treated with modeling techniques indicator 1 produces tcount = 3.57> ttable = 1.94, From this study effective modeling techniques to improve the character able to independent